Applying Patient and Public Involvement in preclinical research: A co‐created scoping review. (10th October 2022) - Carroll, Pádraig; Dervan, Adrian; Maher, Anthony; McCarthy, Ciarán; Woods, Ian; Kavanagh, Rachel; Beirne, Cliff; Harte, Geoff; O'Flynn, Dónal; O'Connor, Cian; McGuire, Tara; Leahy, Liam M.; et al.
Abstract: Background: Patient and Public Involvement (PPI) in research aims to improve the quality, relevance and appropriateness of research. PPI has an established role in clinical research where there is evidence of benefit, and where policymakers and funders place continued emphasis on its inclusion. However, for preclinical research, PPI has not yet achieved the same level of integration. As more researchers, including our team, aim to include PPI in preclinical research, the development of an evidence‐based approach is important. Therefore, this scoping review aimed to identify and map studies where PPI has been used in preclinical research and develop principles that can be applied in other projects. Methods: A scoping review was conducted to search the literature in Medline (PubMed), EMBASE, CINAHL, PsycInfo and Web of Science Core Collection to identify applied examples of preclinical PPI. Two independent reviewers conducted study selection and data extraction separately. Data were extracted relating to PPI in terms of (i) rationale and aims, (ii) approach used, (iii) benefits and challenges, (iv) impact and evaluation and (v) learning opportunities for preclinical PPI. Findings were reviewed collaboratively by PPI contributors and the research team to identify principles that could be applied to other projects. Results: Nine studies were included in the final review with the majority of included studies reporting PPI to improve the relevance of their research, using approaches such as PPI advisory panels and workshops. Researchers report several benefits and challenges, although evidence of formal evaluation is limited. Conclusion: Although currently there are few examples of preclinical research studies reporting empirical PPI activity, their findings may support those aiming to use PPI in preclinical research. Through collaborative analysis of the scoping review findings, several principles were developed that may be useful for other preclinical researchers. Patient or Public Contribution: This study was conducted as part of a broader project aiming to develop an evidence base for preclinical PPI that draws on a 5‐year preclinical research programme focused on the development of advanced biomaterials for spinal cord repair as a case study. A PPI Advisory Panel comprising seriously injured rugby players, clinicians, preclinical researchers and PPI facilitators collaborated as co‐authors on the conceptualization, execution and writing of this review, including refining the findings into the set of principles reported here.